2022
DOI: 10.48550/arxiv.2201.06028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Language Deduction through Search over Statement Compositions

Abstract: In settings from fact-checking to question answering, we frequently want to know whether a collection of evidence entails a hypothesis. Existing methods primarily focus on end-toend discriminative versions of this task, but less work has treated the generative version in which a model searches over the space of entailed statements to derive the hypothesis. We propose a system for natural language deduction that decomposes the task into separate steps coordinated by best-first search, producing a tree of interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…1 Middle). In contrast, stepwise methods generate the proof as individual proof steps, either forward Sanyal et al, 2022;Bostrom et al, 2022) or backward (Dalvi et al, 2022). Our method generates proofs stepwise, in the forward direction.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Middle). In contrast, stepwise methods generate the proof as individual proof steps, either forward Sanyal et al, 2022;Bostrom et al, 2022) or backward (Dalvi et al, 2022). Our method generates proofs stepwise, in the forward direction.…”
Section: Related Workmentioning
confidence: 99%
“…When generating a proof step, prior work has observed that if the hypothesis is available, the model often uses it to hallucinate the intermediate conclusion instead of drawing valid logical inferences (Table 3). Therefore, ProofWriter FaiRR (Sanyal et al, 2022), and SCSearch (Bostrom et al, 2022) explicitly ban the model from accessing the hypothesis when generating intermediate conclusions, forcing it to draw inference from known premises only. However, without the hypothesis, the model may generate many valid proof steps irrelevant to the hypothesis.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations